(untitled) (Journal of Medicine, 2012)
Background : Children emergency unit is a very important in hospitals offering paediatric services. Most of the studies done in Nigeria have been retrospective which most times do not capture the total picture of presentations as some are lost due to poor record keeping. Aim : To determine the true pattern and outcome of presentations at the children emergency unit in our hospital through a prospective study. Materials and Method : All presentations at the children emergency unit of Delta State University Teaching Hospital Oghara since its inception in December 2010 till November 2011 were recorded and all the information about each patient from the biodata to the outcome of each presentation were analysed. Result : A total of five hundred and twenty patients were seen within this period. Non- emergency patients represented 10.2%. There was a male preponderance, and over 90% were five years and below. Malaria was the commonest presentation at 16.7% followed by acute respiratory infections at 14.4%. Mortality was 2.3% with meningitis and severe anaemia each accounting for 33.3%. 66.7% of the total deaths were in infants. Discussion : Malaria is the commonest presentation. Over 10% were cold cases. Triaging will reduce mortality as this will give the emergency physician undistracted attention to more serious patients. Death in infancy still represents the highest contributor to the over- all mortality. Conclusion : Presentation at the children emergency unit has largely remained the same over the years. However prospective studies should always be done to establish true picture of presentation at children emergency units and efforts to select truly emergency patients will help in rendering better services. DOI: http://dx.doi.org/10.3329/jom.v13i2.12753 J Medicine 2012; 13 : 170-173